Analisisa Penerapan Supply Chain Management Pada Kopi Robusta di Kota Sidikalang - Utami R.A Padang; Siti Aisyah (Universitas Muhammadiyah Enrekang, 2022)
The Sidikalang area is indeed known as the best producer of Robusta coffee beans which have high caffeine content, which reaches 70-80%. There are companies that produce and sell products in the form of Robusta coffee. These companies certainly need activities in the form of supply chain management which are applied to the flow of goods from upstream downstream. The company certainly needs activities in the form of supply chain management that is applied to the flow of goods from upstream to downstream. Companies that use good supply chain management will have a good impact on the flow of goods or services. The impact is that the company will be more structured, coordinated, scheduled, and integrated so that the whole process will run effectively and efficiently. Then the company also makes efforts to offer the best products for consumers. This study aims to 1) determine the application of supply chains management and 2) the factors that hinder supply chains management in Robusta coffee in Sidikalang city. The method used is a qualitative research method with a descriptive approach. Data collection techniques by observation, case study and interviews. The results of the study using observation and interview data collection techniques showed that the application of supply chain management to robusta coffee in the city of Sidikalang, namely there was an application of SCM consisting of producers, retailers of robusta coffee are people who already trust and know each other so that it can facilitate and provide smooth operation. for SCM activities on robusta coffee in the city of Sidikalang. And there are factors that hinder SCM activities, namely pest attacks on robusta coffee, labor shortages, and the robusta coffee fields are far from the robusta coffee company factory in Sidikalang city